العمالة المؤنثة في القطاع غير المنظم ودورها على سوق العمل السورية خلال الفترة 2002-2010 - عامر, وليد; العشعوش, أيمن; منصورة, نورا (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف هذا البحث إلى تحليل واقع الإناث في القطاع غير المنظم, وتحديد مدى مساهمتهن في النشاط الاقتصادي, وذلك لتحديد حصة القطاع غير المنظم بالنسبة للإناث في سوق العمل. لاسيما أن ذلك سيوضح إن كان هناك خلل في استقطاب القطاع المنظم للعمالة المؤنثة. وسيتم ذلك من خلال تحليل واقع عمالة الإناث في القطاع المنظم, وتحديد حصتهن من سوق العمل من جهة, وتحديد خصائص المشتغلات في القطاع غير المنظم من جهة ثانية. حيث تعدّ أساساً لوضع السياسات الاقتصادية المستقبلية, وذلك باستخدام المنهج الوصفي التحليلي. وخلص البحث إلى مجموعة من النتائج, أهمها : وجود علاقة ذات دلالة إحصائية بين مساهمة الإناث من القطاع غير المنظم في النشاط الاقتصادي, وعمالتهن في القطاع غير المنظم. تتأثر عمالة الإناث في القطاع غير المنظم بعمر الإناث المشتغلات, والمستوى التعليمي لهن. The purpose of this research is to analyze the reality of the female informal sector, and to determine the female labour, informal sector participation in the economy, which leads to determine the share of informal sector in the labour market. That will illustrate the deficiency of the formal sector in attracting female labour. On one hand, that will be done by analyzing the reality of the informal female labour and determining their share in the labour market, and determining the properties of informal female labour on the other hand. Both of the analyzing and determining will give the future view to help in putting economic policies, using descriptive analytical method. The research found many results, the most important were: • There is a significant relationship between the female labour participation rate and their works in the informal sector. • The informal female labour is affected by age group and educational attainment.